2022
DOI: 10.1186/s12903-022-02292-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral health promotion interventions on pregnant women dental caries: a field trial

Abstract: Background Dental caries is a costly and very common disease, especially in pregnant women. Reasons such as not paying attention to oral health, poor diet and also lack of adequate education in this regard cause this to happen. Performing well-designed educational interventions using primary health system’s forces, can improve oral health of pregnant women and help control this disease. We conducted this study to evaluate the effectiveness of some oral health interventions on pregnant women den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…The results of previous interventional studies were similar to our study [ 12 , 23 , 24 ]. A previous study conducted in Dammam, Saudi Arabia [ 23 ], showed an improvement in health information using social media (Snapchat), similar to our study; however, there are four differences.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of previous interventional studies were similar to our study [ 12 , 23 , 24 ]. A previous study conducted in Dammam, Saudi Arabia [ 23 ], showed an improvement in health information using social media (Snapchat), similar to our study; however, there are four differences.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the findings of this study and prior studies in the literature [ 12 , 23 , 24 ], we suggest that social media can be a useful tool for promoting education about oral health care. Moreover, social media has been found to be another method for teaching in health schools [ 30 , 31 ], which opens new doors to using such powerful technology in positive ways.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…One study used a Telegram channel to deliver oral health education programs, including audio, video, and text messages related to nutrition and behavior. This study concluded that the use of social media alone had an insignificant effect on preventing dental caries among pregnant women when compared to other interventions such as face-to-face education or group discussions, or a combination of interventions [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proper healthy diet during pregnancy represents a positive influence on reducing the gingival and periodontal inflammation [ 12 , 14 ]. As the sugar-rich diet has an influence on the bacterial load, its’ direct effect are dental caries, a common and costly disease in pregnant women [ 15 ]. Findings of the researchers from Pelotas show the far effect of dental caries in this group of patients, discussing that even depression is mediated by self-perception about oral health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%